A state-of-the-art overview on the developing trend of heat transfer enhancement by single-phase flow at micro scale. (November 2019) - Li, Sining; Zhang, Hongna; Cheng, Jianping; Li, Xiaobin; Cai, Weihua; Li, Zengyao; Li, Fengchen
Highlights: Non-Newtonian fluids show a promising topic for futuristic biology and medical area. Mal-distribution effect on heat transfer in the MCHS has been explained. Effects of pulsating inlet flow in laminar flow and acoustic wave on heat transfer are perused. Mechanism of each method and recommendations for further studies are given. Abstract: Continuous improvement of energy-efficient systems has led to various technical features such as miniaturization, integration, and portability. This development became the leading trend of the contemporary industry, with the evolvement of various new and miniaturized instruments such as micro-electro-mechanical systems and micro-satellite. Highly miniaturized and integrated electronic devices often release a large amount of heat within their micro scale inter-components areas, which under certain circumstances, may lead to the micro-device's functional failure. This calls for techno-scientific efforts for efficient heat removal from the mentioned devices. Numerous innovatively scenarios have been so far explored to satisfy the greatly increasing heat removal demand. This paper explores two major types of heat removal technics for micro-scale single-phase flow, namely passive and active type. The passive type includes the geometry modification and working media change, where corresponding effects on heat transfer performance and fluid flow are addressed by Nusselt number and friction factor, respectively. Their most important advantages are stability and robustness in operation or integration with complex systems. For the active type, only the pulsating inlet flow and acoustic wave are considered in the present paper, which are less reviewed recently. Generally, the heat transfer enhancement is attributed to the effect of disturbed thermal boundary layers on mixing of fluids. The present review article is organized in a way that provides a historical perspective of the recent developments in this area, and advances comprehensive comments from overall situations; which may serve a substantial guidance for researchers in different background who intend to step into this area.